Effectiveness of Educational Information Communication (IEC) on Childbirth Preparation to Reduce Anxiety of Third Trimester Pregnant Women in Facing Childbirth - L. Indri Riyanti; Desi Soraya; Qomariyah Qomariyah (Yayasan Cendekia Gagayunan Indonesia, 2025)
Introduction: third-trimester pregnant women at the Karangdoro Health Center in Semarang experience anxiety in facing labour. Stress due to anxiety about facing labour impacts the length of the labour process and the welfare of the fetus. Providing CIE can increase mothers' knowledge and reduce the appearance of psychosocial factors such as ignorance and lack of attention from health workers, which have a negative impact, so that pregnant women are better prepared and anxiety in facing childbirth can be minimized. Objective: to determine the effectiveness of CIE preparation for delivery to reduce anxiety in third-trimester pregnant women facing labour. Method: This study used a quantitative method with a quasi-experimental type of research and a one-group pretest-post-test design. Population: all third-trimester pregnant women at the Karangdoro Health Center Semarangfrom June to July 2023 with 62 respondents. Sample: The sampling technique used accidental sampling and obtained a total sample of 54 respondents. Results: The results of the study were that Communication Information Educational (CIE) for childbirth preparation was effective in reducing anxiety in third-trimester pregnant women facing labour with a value of 0.00 (<0.005), where every single delivery of CIE for childbirth preparation can make third-trimester pregnant women potentially 6,280 times more likely to experience a decrease in the level of anxiety in facing childbirth (Z = 6,280). Of the 54 respondents, 52 (96.3%) experienced a decrease in their level of anxiety, there were no (0%) respondents who experienced an increase in their level of anxiety, and there were 2 (3.7%) respondents with a constant level of anxiety.